Designing climate resilient agricultural systems with some examples from India - Whitbread, Anthony M.; Dhulipala, Ram K.; Nedumaran, Swamikannu; Padhee, Arabinda; Padmaja, Ravula; Rao, Karuturi; Shalander, Kumar; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
For the purposes of this short review, we will focus on CSA as it relates to decisions made at the farm level and may encompass single technological innovations (e.g., a more heat or drought tolerant crop variety), packages of innovations (e.g., a bundle of agronomic practices with climate information for decision-making) through to the design of farms and farming systems to cope with climate variability and extreme events. Examples from semi-arid farming systems in India are used.